Genetic Diversity, Evolutionary Dynamics, and Pathogenicity of Ferret Badger Rabies Virus Variants in Mainland China, 2008–2018 - Miao, Faming; Zhao, Jinghui; Li, Nan; Liu, Ye; Chen, Teng; Mi, Lijuan; Yang, Jinjin; Chen, Qi; Zhang, Fei; Feng, Jie; Li, Shunfei; Zhang, Shoufeng; et al. (Frontiers in Microbiology, 2022)
In contrast to dog associated human rabies cases decline year by year due to the rabies vaccination coverage rates increase in China, ferret badger (FB, Melogale moschata)–associated human rabies cases emerged in the 1990s, and are now an increasingly recognized problem in southeast China. To investigate epidemiology, temporal evolution dynamics, transmission characterization and pathogenicity of FB-associated rabies viruses (RABVs), from 2008 to 2018, we collected 3,622 FB brain samples in Jiangxi and Zhejiang Province, and detected 112 RABV isolates. Four FB-related lineages were identified by phylogenetic analysis (lineages A–D), the estimated Times to Most Recent Common Ancestor were 1941, 1990, 1937 and 1997 for lineages A–D respectively. Furthermore, although no FB-associated human rabies case has been reported there apart from Wuyuan area, FB-RABV isolates are mainly distributed in Jiangxi Province. Pathogenicity of FB-RABVs was assessed using peripheral inoculation in mice and in beagles with masseter muscles, mortality-rates ranging from 20% to 100% in mice and 0 to 20% in beagles in the groups infected with the various isolates. Screening of sera from humans with FB bites and no postexposure prophylaxis to rabies, revealed that 5 of 9 were positive for neutralizing antibodies of RABV. All the results above indicated that FB-RABV variants caused a lesser pathogenicity in mice, beagles and even humans. Vaccination in mice suggests that inactivated vaccine or recombinant subunit vaccine products can be used to control FB- associated rabies, however, oral vaccines for stray dogs and wildlife need to be developed and licensed in China urgently.